Professional Competencies in Intensive Care and Emergency Medicine at the Faustino Pérez Provincial Clinical Surgical Teaching Hospital - Díaz-Luis, Olimpia; Ojeda-Martell, Rolando Ernesto; Secada-Cárdenas , Eneyda (Revista Científica Estudiantil de Ciencias Médicas de Matanzas, 2026)
The article addresses the urgent need to develop comprehensive professional competencies in the training of specialists in Intensive Care and Emergency Medicine. It highlights that, beyond theoretical knowledge, it is essential to foster practical skills, management, leadership, communication, and ethics in high-pressure environments. It proposes implementing a contextualized didactic strategy that integrates continuous assessment, simulation, and reflection, placing the resident at the center of their learning. The research objective is to substantiate the need for a competency-based training strategy to enhance the quality and safety of critical care, ensuring holistically prepared professionals.